Influência do espaçamento, população de plantas e híbridos na intensidade de doenças e fatores de produção de milho safrinha - Fontoura, Darci da (2005)
Although the safrinha (short season) corn area had almost a tenfold increase during the last 15 years, few studies were reported on this specific environment. The objective of the current study was to evaluate the effect of the spatial arrangement created by row spacing or by plant population on corn disease intensity in the safrinha environment. The experiment was installed in Toledo/PR for two consecutive years, 2004 and 2005. It was a randomized complete block design with 4 replications, on a factorial scheme with hybrid as the first factor (X1392D, 30F80, 30K75 and 30P70) and row spacing (38 cm, mix with 38 and 76 cm or 76 cm) or plant population (45, 60 and 75 thousand plants ha-1) as the second factor. The hybrids were selected in order to fill the following requirements: two of them had erect leaf architecture and the other two had horizontal leaf architecture, besides a different tolerance level for the main corn diseases. The incidence and severity of the leaf, stalk and ear pathogenic fungus, the incidence of generic parameters as kernel rot, root lodging, stalk lodging, besides the production factors and productivity were evaluated. Although higher plant populations and narrower row spacing resulted in higher disease intensity, there was a tendency of better yields under these treatments. On the other hand, it was dependant on the hybrid and climate condition of each growing year. The internal temperature of each plot was not affected by the spatial arrangement, however the leaf architecture affected the maximum temperature, even though it was not directly related to the disease intensity